The reproducibility of shear wave and strain elastography in epidermal cysts - Kim, Ji Na; Park, Hee Jin; Kim, Myung Sub; Won, So Yeon; Song, Eunhee; Kim, Minchul; Shin, Hyunchul (Ultrasonography (Seoul, Korea), 2022)
Purpose: This study evaluated epidermal cyst elasticity using multiple parameters of strain elastography (SE) and shear wave elastography (SWE) and assessed the reproducibility of each parameter.Methods: This retrospective study included 73 patients with epidermal cysts who underwent SE and SWE. SE scores were classified as 1-4 according to elasticity. The strain ratio was evaluated using the elasticity ratio of lesions and adjacent subcutaneous fat tissue. For SWE, the shear wave velocity (m/s), elasticity (kPa) according to the Young modulus, velocity ratio, and elasticity ratio were evaluated. All values were measured twice. The reproducibility of SE and SWE measurements was assessed. The relationships among SE and SWE measurements were evaluated.Results: The strain ratio on SE images showed good reproducibility (intra-class correlation coefficient [ICC]=0.789), and SE scores showed substantial reproducibility (kappa=0.753 and kappa=0.758 for readers 1 and 2, respectively). Moderate reproducibility was found for shear wave velocity and elasticity (ICC=0.750 and ICC=0.648, respectively), as well as for the shear wave velocity of the reference tissue and velocity ratio (ICC=0.747 and ICC=0.713, respectively). All SE scores were positively correlated with the strain ratio (P<0.001). The strain ratio in the second SE session was significantly correlated with the elasticity ratio and velocity ratio in the first SWE session (r=0.245, P=0.037; r=0.243, P=0.038, respectively). Other variables were not correlated.Conclusion: SE and SWE parameters of epidermal cysts showed moderate to good reproducibility. The strain ratio on SE showed good reproducibility and could provide relatively objective and consistent measurements of epidermal cyst elasticity.